2016
DOI: 10.1111/ijfs.13092
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of chickpea flour‐based gluten‐free batters and muffins with added biopolymers: rheological, physical and sensory properties

Abstract: Chickpea flour (CF)-based muffin formulations were made with CF alone and with added biopolymers [whey protein (WP), xanthan gum (XG) and inulin (INL)] to evaluate their suitability to be a wheat flour (WF) substitute in muffins. Structural characteristics of the batters and muffins were studied by means of rheometry, microscopy, physicochemical properties, and texture and sensory analysis. Partial replacement of CF with XG, alone (at 0.5 and 1%) or blended with either WP or INL, significantly increased the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 22 publications
5
45
0
4
Order By: Relevance
“…As expected, wheat flour cake had the highest volume 375 cm 3 These results are in agreement with Gomez et al, [40] and Herranz, et al, [12] as they reported that supplemented of cakes with chickpea flour resulted in lower gas retention and lower expansion of cake and the volume was decreased with increasing levels of chickpea flour.…”
Section: Specific Gravitysupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, wheat flour cake had the highest volume 375 cm 3 These results are in agreement with Gomez et al, [40] and Herranz, et al, [12] as they reported that supplemented of cakes with chickpea flour resulted in lower gas retention and lower expansion of cake and the volume was decreased with increasing levels of chickpea flour.…”
Section: Specific Gravitysupporting
confidence: 89%
“…Additionally, germinated seeds contain significant amounts of polyphenols with well pro-health properties [11] [12]. Hydrocolloids (such as xanthan gum, guar gum and pectin) are added to naturally gluten-free flour to mimic the viscoelastic properties of gluten and to improve sensory properties, structure, and shelf-life of these products [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…People suffering for celiac disease are unable to consume them because they are traditionally prepared from wheat flour with added eggs, sugar, oil or fat and milk, yeasts or baking powder. Nowadays, scientific data is available regarding gluten-free muffins prepared from different types of flours, like chickpea (Herranz et al 2016), rice (Nozawa et al 2016;Singh et al 2015Singh et al , 2016, corn (Marcet et al 2015) or buckwheat (Ciesarová et al 2016). Also protease treatment is used to produce wheat flour with partially hydrolysed gluten that may be used for preparing hypoimmunogenic muffins as presented by Umashankar et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…[8] The authors just cited studied the effect on muffin batter rheological properties of replacing WF with CF and then studied the addition of biopolymers (whey protein, xanthan gum, and inulin) to CF-based muffin formulations, either alone or blended, to evaluate their suitability as a substitute for WF in muffins. [7] Wheat-free muffin batter had the lowest viscoelasticity and the highest viscosity because of higher intermolecular aggregation interactions due to higher protein content. The addition of xanthan gum to CF-based batters increased the elastic character of the batters at 25°C and during non-isothermal heating in comparison with control wheat muffin batters.…”
Section: Introductionmentioning
confidence: 99%
“…The hope of IYP 2016 is to position pulses as primary sources of protein and other essential nutrients, leading to dietary uptake. [6][7][8] Chickpea (Cicer arietinum L.) is a legume rich in protein, dietary fibre, carbohydrates, folate, and trace minerals (Fe, Mo, Mn). [9] Flatus production is considered to be the most important factor that dissuades people from eating this grain legume, but recent research shows that α-galactosides may also have a beneficial effect by increasing the bifidobacteria population in the colon.…”
Section: Introductionmentioning
confidence: 99%